Effectiveness of Legal Protection Against Misuse of Personal Data in Peer-To-Peer Lending Fintech Services Based on Law Number 27 Of 2022 on Personal Data Protection - Alfinda Salsabila, Uly; Budi Kharisma, Dona (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study analyzes the effectiveness of legal protection against the misuse of consumers' personal data in the digital financial services sector. The research is motivated by the increasing incidents of data breaches and misuse of personal data that harm consumers, while also examining the capability of existing regulations to provide adequate protection. This study evaluates the effectiveness of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). The research employs a normative legal research method with a statutory and conceptual approach. Primary data is derived from Law Number 27 of 2022 on Personal Data Protection (PDP Law), while secondary data comes from relevant legal literature. This research is important due to the growing problem of personal data misuse in fintech P2P lending services, which is rapidly expanding, thus necessitating more specific regulatory updates to keep up with technological developments in fintech in general. The purpose of this study is to analyze the effectiveness of the implementation of Law No. 27 of 2022 in regulating personal data protection and the sanctions imposed on parties involved in the misuse of personal data. This indicates that although legal instruments for data protection are available, their implementation still faces obstacles, particularly in terms of oversight and law enforcement, which remain weak. Therefore, this study concludes that regulatory harmonization, strengthening the role of supervisory institutions, and raising legal awareness are necessary.